Method for manufacturing ceramic sheet and degreased body of ceramic sheet
Patent Information
- Application Number
- JP2023140171
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-30
- Publication Date
- 2025-03-13
AI Technical Summary
【0008】 本開示の一側面によれば、うねりの発生を抑制可能なセラミックシートの製造方法及びセラミックシートの脱脂体を提供できる。
Smart Images

Figure 2025034040000002 
Figure 2025034040000003 
Figure 2025034040000004
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a method for manufacturing a ceramic sheet and a degreased ceramic sheet. [Background technology]
[0002] Ceramics are widely used in many fields because they have excellent mechanical properties such as heat resistance and wear resistance, as well as electrical and magnetic properties and biocompatibility. Among them, ceramics mainly composed of zirconia have excellent oxygen ion conductivity. Therefore, sheet-shaped molded bodies (ceramic sheets) of the ceramics are sometimes used as solid electrolytes in solid oxide fuel cells (SOFCs).
[0003] From the viewpoint of improving the performance of SOFCs, it is desirable to make the ceramic sheet as described above thinner. However, if the thickness is simply reduced, the sheet is more likely to crack. For this reason, it is also desirable to improve the mechanical strength of the ceramic sheet. For example, in the following Patent Document 1, an attempt is made to improve the mechanical strength of the sheet by reducing the residual pores in the sheet. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2011-204398 A Summary of the Invention [Problem to be solved by the invention]
[0005] The thinner the ceramic sheet, the more likely it is that the sheet will undulate. For example, ceramic sheets for solid electrolytes in SOFCs require high flatness, so the occurrence of undulations as described above is a factor in reducing yields.
[0006] An object according to one aspect of the present disclosure is to provide a method for manufacturing a ceramic sheet and a degreased ceramic sheet capable of suppressing the occurrence of waviness. [Means for solving the problem]
[0007] One aspect of the present disclosure provides a method for producing a ceramic sheet and a degreased ceramic sheet as set forth in the following [1] to [9]. [1] A method for producing a ceramic sheet, comprising the steps of: preparing a slurry by mixing a ceramic powder, a solvent and a binder; forming a green sheet by applying the slurry to a sheet and then drying the sheet; degreasing the green sheet to form a degreased body of the green sheet; sintering the degreased body to form a ceramic sheet; Equipped with When the pore size distribution of the degreased body is measured by mercury intrusion porosimetry, the total volume of the pores of the degreased body in the pore size range of 0.003 μm or more and 1 μm or less is 0.17 ml / g or more and 0.23 ml / g or less; The total volume of pores having a pore diameter of 0.015 μm or more and 1 μm or less, which is smaller than the mode diameter of the pores in the above range, is 5% or more and 40% or less of the total volume. A method for manufacturing a ceramic sheet. [2] A method for producing a ceramic sheet, comprising the steps of: preparing a slurry by mixing a ceramic powder, a solvent and a binder; forming a green sheet by applying the slurry to a sheet and then drying the sheet; degreasing the green sheet to form a degreased body of the green sheet; sintering the degreased body to form a ceramic sheet; Equipped with When the pore size distribution of the degreased body is measured by mercury intrusion porosimetry, the total volume of the pores of the degreased body in the pore size range of 0.003 μm or more and 1 μm or less is 0.17 ml / g or more and 0.23 ml / g or less; In the cumulative pore size distribution, the cumulative pore size of 5% of the volume from the largest pore is defined as D5. When the cumulative 50% pore diameter is defined as D50 and the cumulative 95% pore diameter is defined as D95, (D5-D95) / D50≧0.56 is satisfied. A method for manufacturing a ceramic sheet. [3] The method for producing a ceramic sheet according to [1] or [2], wherein the ceramic powder is a stabilized zirconia powder containing at least one rare earth element selected from the group consisting of scandium, yttrium, and cerium in a total amount calculated on the oxide of 3 mol % or more and 15 mol % or less. [4] The method for producing a ceramic sheet according to any one of [1] to [3], wherein the sintering temperature in the step of sintering the degreased body is 1300° C. or higher and 1500° C. or lower. [5] The method for producing a ceramic sheet according to [4], wherein in the step of sintering the degreased body, the time required for heating from the temperature immediately after the step of forming the degreased body to the sintering temperature is 8 hours or more and 20 hours or less. [6] The method for producing a ceramic sheet according to any one of [1] to [5], wherein the ceramic sheet has a relative density of 98% or more. [7] The method for producing a ceramic sheet according to any one of [1] to [6], wherein the ceramic sheet has a thickness of 50 μm or more and 200 μm or less. [8] A degreased body of a green sheet, When the pore size distribution of the degreased body is measured by mercury intrusion porosimetry, the total volume of the pores of the degreased body in the pore size range of 0.003 μm or more and 1 μm or less is 0.17 ml / g or more and 0.23 ml / g or less; The total volume of pores having a pore diameter of 0.015 μm or more and 1 μm or less, which is smaller than the mode diameter of the pores in the above range, is 5% or more and 40% or less of the total volume. Defatted body. [9] A degreased body of a green sheet, When the pore size distribution of the degreased body is measured by mercury intrusion porosimetry, the total volume of the pores of the degreased body in the pore size range of 0.003 μm or more and 1 μm or less is 0.17 ml / g or more and 0.23 ml / g or less; In the cumulative pore size distribution, when the cumulative 5% pore size based on the volume from the largest pore is defined as D5, the cumulative 50% pore size is defined as D50, and the cumulative 95% pore size is defined as D95, (D5-D95) / D50≧0.56 is satisfied. Defatted body. Effect of the Invention
[0008] According to one aspect of the present disclosure, it is possible to provide a method for manufacturing a ceramic sheet and a degreased ceramic sheet capable of suppressing the occurrence of waviness. [Brief description of the drawings]
[0009] [Figure 1] FIG. 1 is a flowchart illustrating a method for manufacturing a ceramic sheet according to an embodiment. [Diagram 2] FIG. 2 is a diagram showing the pore size distribution of each of the examples and comparative examples. [Diagram 3] FIG. 3 is a diagram showing the cumulative pore size distribution of each of the examples and comparative examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] One embodiment of the present disclosure will be described in detail below, but the present disclosure is not limited thereto.
[0011] Hereinafter, a method for manufacturing a ceramic sheet according to an embodiment will be described in detail with reference to Fig. 1. Fig. 1 is a flow chart for explaining a method for manufacturing a ceramic sheet according to an embodiment. Note that the ceramic sheet according to an embodiment is a solid electrolyte (electrolyte sheet) for a solid oxide fuel cell (hereinafter, referred to as "SOFC"), but the ceramic sheet of the present disclosure is not limited to a solid electrolyte for SOFC.
[0012] As shown in FIG. 1, first, a slurry is prepared by mixing ceramic powder, a solvent, and a binder (first step ST1). In the first step ST1, for example, a grinding device such as a ball mill, a bead mill, a planetary mill, or a jet mill is used to mix the ceramic powder, the solvent, and the binder, to prepare a slurry. For example, the ceramic powder, the solvent, and the binder are mixed in the grinding device for 10 minutes or more and 5000 minutes or less. If the dispersibility of the ceramic powder in the slurry is low, a large amount of pores (voids) are formed in the ceramic sheet. This tends to make it difficult to obtain desired performance such as mechanical strength and oxygen ion conductivity. On the other hand, if the dispersibility of the ceramic powder in the slurry is too high, the ceramic sheet tends to easily become wavy. Therefore, in one embodiment, from the viewpoint of the dispersibility of the ceramic powder in the slurry, the grinding time is, for example, 15 minutes or more and 2000 minutes or less. The grinding time may be 30 minutes or less, 25 minutes or less, or 20 minutes or less. In the first step ST1, a defoaming treatment of the slurry may be performed by a known method.
[0013] The ceramic powder is a raw material that is a main component of the ceramic sheet, and contains at least one type of powder. The powder contained in the ceramic powder is appropriately selected according to the ceramic sheet to be manufactured. When the ceramic sheet to be manufactured is a solid electrolyte for SOFC, the ceramic powder is a raw material for the solid electrolyte. When the ceramic powder contains multiple types of powder, the powders may be mixed together with a solvent and a binder, or may be mixed in advance before mixing with the solvent and the binder.
[0014] The ceramic powder may be a powder in which at least one selected from CaO, SrO, BaO, Y2O3, La2O3, Ce2O3, Pr2O3, Nd2O3, Sm2O3, Eu2O3, Gd2O3, Tb2O3, Dr2O3, Ho2O3, Er2O3, Yb2O3, PbO, WO3, MoO3, V2O5, Ta2O5, Nb2O5, etc. is added to a ceria-based oxide such as CeO2 or a bismuth-based oxide such as Bi2O3. The ceramic powder may further contain a gallate-based oxide such as LaGaO3.
[0015] In one embodiment, the ceramic powder includes a powdered zirconia-based ceramic. The zirconia-based ceramic is, for example, zirconia containing a stabilizer. The stabilizer includes at least one selected from alkaline earth metal oxides such as MgO, CaO, SrO, and BaO; rare earth element oxides such as Sc2O3, Y2O3, La2O3, CeO2, Pr2O3, Nd2O3, Sm2O3, Eu2O3, Gd2O3, Tb2O3, Dy2O3, Ho2O3, Er2O3, and Yb2O3; and oxides such as Bi2O3 and In2O3. The zirconia-based ceramic may include oxides such as Al2O3, SiO2, Ge2O3, B2O3, SnO2, Ta2O5, and Nb2O5 as additives.
[0016] From the viewpoint of oxygen ion conductivity, strength, toughness, etc., the zirconia-based ceramic may be a stabilized zirconia powder containing at least one rare earth element selected from the group consisting of scandium, yttrium, cerium, gadolinium, and ytterbium in a total amount of 0.5 mol% to 20 mol% or 3 mol% to 15 mol% calculated on oxide basis. When scandium is included as a rare earth element, the stabilized zirconia-based ceramic may be called scandia-stabilized zirconia (ScSZ). When yttrium is included as a rare earth element, the stabilized zirconia-based ceramic may be called yttria-stabilized zirconia (YSZ). When scandium and cerium are included as rare earth elements, the stabilized zirconia-based ceramic may be called scandia-ceria-stabilized zirconia (ScCeSZ). The stabilized zirconia ceramic can be obtained, for example, by heat-treating a mixture of commercially available zirconia powder and a powdered rare earth element, followed by pulverizing the mixture. The heat-treated mixture may be a pre-fired or sintered compact of commercially available zirconia powder and a powdered rare earth element.
[0017] The stabilized zirconia powder may be a cubic stabilized zirconia powder or a tetragonal stabilized zirconia powder. The cubic zirconia powder is a powder containing cubic zirconia as a zirconia-based oxide as a main component (main crystal phase). Cubic zirconia is a substance in which a line peak attributed to cubic zirconia is observed by X-ray diffraction. The tetragonal zirconia powder is a powder containing tetragonal zirconia as a zirconia-based oxide as a main component (main crystal phase). Tetragonal zirconia is a substance in which a line peak attributed to tetragonal zirconia is observed by X-ray diffraction.
[0018] In one embodiment, a cubic zirconia powder or a tetragonal zirconia powder satisfying a specific particle size distribution may be used as the raw zirconia powder. When a cubic zirconia powder is used as the raw zirconia powder, the cubic crystal ratio (%) of the powder is, for example, 50% or more. The cubic crystal ratio may be 60% or more, 80% or more, 90% or more, or 95% or more. When a tetragonal zirconia powder is used as the raw zirconia powder, the tetragonal crystal ratio (%) of the powder is, for example, 50% or more. The tetragonal crystal ratio may be 60% or more, 80% or more, 90% or more, or 95% or more. The average primary particle diameter of the cubic zirconia powder or the tetragonal zirconia powder may be, for example, 0.003 μm or more and 0.2 μm or less, or 0.005 μm or more and 0.15 μm or less. The average primary particle size is calculated, for example, from the results of measurement using a transmission electron microscope. When the raw zirconia powder is a cubic zirconia powder or a tetragonal zirconia powder, the raw zirconia powder may contain a stabilizer or the like as necessary.
[0019] In addition to the zirconia powder, the ceramic powder may contain powders of alumina, ceria, titania, silica, niobium oxide, thallium oxide, mullite, cordierite, spinel, forsterite, anorthite, celsian, enstatite, aluminum nitride, silicon nitride, etc., within a range that does not impair the desired effect. The content of the powder may be, for example, 0.01% by mass or more and 5% by mass or less, or 0.05% by mass or more and 3% by mass or less, based on the total amount of the raw material powders.
[0020] The 50 volume % diameter (D50) of the ceramic powder is, for example, 0.05 μm or more and 0.8 μm or less, and the 90 volume % diameter (D90) is, for example, 0.3 μm or more and 1.5 μm or less. When D90 is 1.5 μm or less, the aggregates of the ceramic powder are unlikely to become excessively large. Therefore, the obtained ceramic sheet is well densified. On the other hand, when D90 is 0.3 μm or more, the dispersibility of the ceramic powder during the preparation of the slurry is good. D90 may be 0.5 μm or more, 0.6 μm or more, 1.0 μm or less, or 0.8 μm or less. The 10 volume % diameter (D10) of the ceramic powder is, for example, 0.03 μm or more and 0.6 μm or less. In this case, since there are few fine particles in the ceramic powder, the occurrence of local sintering, non-uniform sintering, etc. can be reduced. D10 may be 0.06 μm or more, 0.1 μm or more, 0.6 μm or less, 0.5 μm or less, or 0.4 μm or less. As described above, by controlling the particle size distribution of the ceramic powder (i.e., at least one of D10, D50, and D90), decomposition gases of organic matter are efficiently released during degreasing of the green sheet, and stress relaxation during sintering is also improved.
[0021] The 50% by volume diameter (D50) is measured by a laser diffraction / scattering type particle size distribution measuring device (manufactured by Horiba, Ltd., product name "LA-920"), and is the value of the particle diameter that is 50% by volume of the total particle volume when the particle volume is integrated from the smallest particle diameter. Similarly, the 90% by volume diameter and the 10% by volume diameter are the particle diameter values that are 90% by volume and 10% by volume of the total particle volume when the particle volume is integrated from the smallest particle diameter. The particle size distribution of the ceramic powder can be adjusted by a combination of grinding using a ball mill, bead mill, planetary mill, jet mill, etc., classification using a cyclone type classifier, etc. Also, a commercially available product having a desired particle size distribution may be used.
[0022] The BET specific surface area of a ceramic powder is, for example, 3 m 2 / g or more 18m 2 / g or less. In this case, it is easy to control the amount of binder required for green sheet formation and the slurry viscosity. 2 / g or more, or 5m 2 / g or more, or 16m 2 / g or less, or 14m 2 / g or less.
[0023] In the slurry, aggregate particles of ceramic powder such as the stabilized zirconia powder may be present. In other words, the slurry may be prepared so that the aggregate particles are present. The aggregate particles are primary particles bound together and may behave as particles in the slurry. The particle size of the aggregate particles in the slurry is, for example, 0.03 μm or more and 4.0 μm or less. The upper limit of the particle size may be 3.0 μm or 2.0 μm.
[0024] There is no restriction on the type of solvent contained in the slurry, and it can be appropriately selected from solvents used in the conventional production of ceramic sheets. Examples of the solvent include water; alcohols such as ethanol, 2-propanol, 1-butanol, and 1-hexanol; ketones such as acetone and 2-butanone; aliphatic hydrocarbons such as pentane, hexane, and heptane; aromatic hydrocarbons such as benzene, toluene, xylene, and ethylbenzene; and acetates such as methyl acetate, ethyl acetate, and butyl acetate. The above solvents may be used alone or in combination of two or more. The content of the solvent is appropriately adjusted in consideration of the viscosity of the slurry, the dispersibility of the ceramic powder in the slurry, and the like. For example, the content of the solvent is adjusted so that the slurry viscosity is in the range of 1 to 20 Pa·s (10 to 200 poise) or 1 to 5 Pa·s (10 to 50 poise). The content ratio of the solvent to the total mass of the slurry is, for example, 20 mass% or more and 50 mass% or less. The content of the alcohol (preferably 1-butanol) relative to the total mass of the solvent may be, for example, 2% by mass or more and 70% by mass or less.
[0025] There is no limitation on the type of binder used in the slurry, and it can be appropriately selected from organic binders and inorganic binders used in the conventional production of ceramic sheets.
[0026] Examples of organic binders include ethylene-based copolymers, styrene-based copolymers, acrylate-based and methacrylate-based copolymers, vinyl acetate-based copolymers, maleic acid-based copolymers, vinyl acetal-based resins, vinyl formal resins, polyvinyl butyral resins, vinyl alcohol-based resins, celluloses such as ethyl cellulose, and waxes. Among these, from the viewpoints of moldability and / or strength of the green sheet, and particularly thermal decomposition during mass firing for mass production, organic binders such as methyl acrylate, ethyl acrylate, propyl acrylate, butyl acrylate, alkyl acrylates having an alkyl group of 10 or less carbon atoms such as isobutyl acrylate, cyclohexyl acrylate, and 2-ethylhexyl acrylate; alkyl acrylates having 20 or less carbon atoms such as methyl methacrylate, ethyl methacrylate, propyl methacrylate, butyl methacrylate, isobutyl methacrylate, cyclohexyl methacrylate, 2-ethylhexyl methacrylate, dodecyl methacrylate, and lauryl methacrylate. The organic binder may be a polymer or copolymer obtained by polymerizing or copolymerizing at least one of the following: alkyl methacrylates having a hydroxyalkyl group; hydroxyalkyl acrylates or hydroxyalkyl methacrylates having a hydroxyalkyl group such as hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate, and hydroxypropyl methacrylate; aminoalkyl acrylates or aminoalkyl methacrylates such as dimethylaminoethyl acrylate and dimethylaminoethyl methacrylate; and carboxyl group-containing monomers such as acrylic acid, methacrylic acid, maleic acid, and maleic acid half esters such as monoisopropyl maleate. The number average molecular weight of the organic binder may be 20,000 or more and 200,000 or less, or 50,000 or more and 100,000 or less. The organic binder may be the above polymer or copolymer used alone, or two or more of them may be used in appropriate combination as necessary. The organic binder may be a copolymer of a monomer containing 60 mass% or more of isobutyl methacrylate and / or 2-ethylhexyl methacrylate.
[0027] As the inorganic binder, for example, at least one selected from zirconia sol, silica sol, alumina sol, titania sol, and the like can be used.
[0028] The mass ratio of the ceramic powder to the binder in the slurry is not particularly limited. For example, the binder may be 5 to 30 parts by mass, or 10 to 20 parts by mass, relative to 100 parts by mass of the ceramic powder. The content of the binder in the slurry is appropriately selected in consideration of the particle size of the ceramic powder, the strength and flexibility required for the ceramic sheet to be manufactured, and the like.
[0029] The slurry may further contain a dispersant, a plasticizer, a lubricant, a surfactant, and / or an antifoaming agent, etc., as necessary. The dispersant is added, for example, to adjust the dispersibility of the ceramic powder in the slurry. The dispersant may be added to promote the deflocculation of the ceramic powder in the slurry. Examples of the dispersant include polymer electrolytes such as polyacrylic acid and ammonium polyacrylate; partial esters of α-olefin-maleic anhydride copolymers; organic acids such as citric acid and tartaric acid; copolymers of isobutylene or styrene and maleic anhydride and their ammonium salts or amine salts; copolymers of butadiene and maleic anhydride and their ammonium salts, etc. From the viewpoint of the dispersibility of the ceramic powder in the slurry, the content of the dispersant in the slurry may be, for example, 3 parts by mass or less, 2.5 parts by mass or less, 2 parts by mass or less, or 1.8 parts by mass or less. The content of the dispersant may be adjusted depending on the type of ceramic powder. The plasticizer is added, for example, to impart flexibility to the green sheet. Examples of the plasticizer include phthalate esters such as dibutyl phthalate and dioctyl phthalate; phthalate polyesters; glycols such as propylene glycol; and glycol ethers.
[0030] Next, the slurry is coated in a sheet form and then dried to form a green sheet (second step ST2). In the second step ST2, the slurry is first coated on a base film. The coated slurry is then dried to form a green sheet on the base film. Examples of methods for coating the slurry on the green sheet include tape casting. This allows the slurry to be continuously coated on the base film. The tape casting method is a method for coating the slurry in a sheet form, and examples of the method include doctor blade. In the tape casting method, for example, pressure is applied to the slurry in a slurry tank to transport the slurry to a coating dam through a pipe. Then, the slurry is coated on the base film. At this time, the thickness of the coated slurry becomes uniform by using the doctor blade method. The material of the polymer film is not particularly limited, and in the second step ST2, a screen printing method may be performed, or a slot die coater, a lip coater, a gravure coater, or the like may be used.
[0031] The base film may be, for example, a resin film such as a polyethylene terephthalate (PET) film that has a predetermined thickness and is flexible. If a long base film is used, a long green sheet can be obtained. The long green sheet may be cut to a predetermined size in the second step ST2 by punching or the like. Alternatively, the long green sheet may be cut to a predetermined size after the second step ST2. The shape of the green sheet is rectangular in plan view, but is not limited thereto. The shape of the green sheet after cutting may be circular, elliptical, or polygonal in plan view. The area of the green sheet in plan view is 100 cm. 2 More than 200cm is fine. 2 More than 400cm is fine. 2 More than 500cm is fine. 2 The thickness of the green sheet is, for example, 50 μm or more and 300 μm or less.
[0032] Next, the green sheet is degreased to form a degreased body of the green sheet (third step ST3). In the third step ST3, first, the green sheet is peeled off from the base film. Then, the green sheet is heat-treated to form a degreased body from which organic components (binder and other organic additives) in the green sheet have been removed. The heat treatment is not particularly limited, and a conventionally known method can be used. For example, the heat treatment may be performed with the green sheets placed one by one on a shelf (setter), or with a laminate in which the green sheets and the spacer sheets are alternately stacked on the shelf. From the viewpoint of preventing adhesion between the green sheet and the spacer sheet, an organic powder may be sprinkled on the green sheet. Examples of the organic powder include natural organic powder such as cornstarch, and synthetic organic resin powder such as melamine cyanurate.
[0033] In the third step ST3, a tunnel-type continuous heating furnace is used in relation to the fourth step ST4 described later, but is not limited to this. In the third step ST3, a batch-type heating furnace may be used. When a tunnel-type continuous heating furnace is used, the third step ST3 is performed in one part of the continuous heating furnace, and the fourth step ST4 is performed in another part of the continuous heating furnace. The third step ST3 is performed, for example, in an air atmosphere or a low-oxygen concentration atmosphere.
[0034] The conditions of the heat treatment in the third step ST3 are not particularly limited, and are set to, for example, known conditions. For example, the green sheet is heated at a heat treatment temperature of 100° C. or more and 450° C. or less for about 2 hours or more and 50 hours or less to form a degreased body. From the viewpoint of suppressing waviness of the ceramic sheet, the burnout rate of the organic components (the release rate of decomposition gas) in the third step ST3 may be made uniform over the entire surface of the green sheet. From the viewpoint of mass productivity of the ceramic sheet, suppression of waviness, etc., the average heating rate in the degreasing treatment temperature range may be controlled to 0.01° C. / min or more and 5° C. / min or less. The average heating rate may be 0.05° C. / min or more and 3° C. / min or less, or 0.1° C. / min or more and 2° C. / min or less. The degreasing treatment temperature range corresponds to the temperature range when the organic components contained in the green sheet are burned and reduced to 10% by mass to 90% by mass with respect to the total amount of the organic components.
[0035] The degreased body formed in the third step ST3 is an intermediate of the ceramic sheet, and corresponds to a sheet-like member obtained by removing organic components from a green sheet. Although not shown, the degreased body has relatively large pores. The diameter of the pores is, for example, 0.03 μm or more and 1 μm or less. The density of the degreased body is, for example, 30% or more and 60% or less of the density of the sintered body. For example, the method of preparing the slurry is adjusted (particularly, the dispersibility of the ceramic powder in the slurry is adjusted) so that the pores are provided in the degreased body. In one embodiment, the pore diameter of the degreased body is measured by mercury intrusion porosimetry. Mercury intrusion porosimetry is a method of determining the pore diameter distribution from the pressure and the amount of mercury intrusion when mercury is injecting into pores or gaps on the surface of a solid.
[0036] In one embodiment, when the pore size distribution of the degreased body is measured by mercury intrusion porosimetry, the total volume of the pores of the degreased body in the pore diameter range of 0.003 μm to 1 μm is 0.17 ml / g to 0.23 ml / g, and the total volume of the pores having a pore diameter of 0.015 μm to 1 μm smaller than the mode diameter of the pores in the above range is 5% to 40% of the total volume. In this case, the degreased body has relatively large pores in a suitable range. The total volume may be 7% or more, 15% or more, 20% or more, 35% or less, 30% or less, or 25% or less of the total volume.
[0037] In one embodiment, when the pore size distribution of the degreased body is measured by mercury intrusion porosimetry, the total volume of the pores of the degreased body in the pore size range of 0.003 μm to 1 μm is 0.17 ml / g to 0.23 ml / g, and in the cumulative pore size distribution, when the cumulative 5% pore size based on the volume from the largest pore is D5, the cumulative 50% pore size is D50, and the cumulative 95% pore size is D95, the relationship (D5-D95) / D50≧0.56 is satisfied. In this case, the degreased body also has relatively large pores in a suitable range. (D5-D95) / D50 is, for example, 0.59 or more. The upper limit of (D5-D95) / D50 is not particularly limited, but is, for example, 0.70 or less.
[0038] When the pore size distribution of a degreased body having a pore size of 0.003 μm or more and 1 μm or less is measured by mercury intrusion porosimetry, if the total volume of the pores is 0.17 ml / g or more and 0.23 ml / g or less and the cumulative pore size distribution satisfies "(D5-D95) / D50≧0.56", the total volume of pores having a pore size smaller than the mode diameter of the pores by 0.015 μm or more and 1 μm or less may be within the range of 5% to 40% of the total volume, or may be outside the range. Similarly, when the pore size distribution of a degreased body having a pore size of 0.003 μm or more and 1 μm or less is measured by mercury intrusion porosimetry, if the total volume of the pores is 0.17 ml / g or more and 0.23 ml / g or less, and the total volume of pores having a pore size smaller than the mode diameter of the pores by 0.015 μm or more and 1 μm or less is 5% or more and 40% or less of the total volume, the cumulative pore size distribution may or may not satisfy "(D5-D95) / D50≧0.56".
[0039] Next, the degreased body is sintered to form a ceramic sheet (fourth step ST4). In the fourth step ST4, the degreased body is fired at high temperature to form a ceramic sheet, which is a sintered body having a desired crystal structure. In one embodiment, the degreased body is fired by the tunnel furnace type continuous heating furnace used in the third step ST3, but is not limited to this. In the fourth step ST4, a batch type heating furnace may be used. When a tunnel furnace type continuous heating furnace is used, the third step ST3 is performed in one part of the continuous heating furnace, and the fourth step ST4 is performed in another part of the continuous heating furnace.
[0040] The firing conditions in the fourth step ST4 are not particularly limited and are set to known conditions, for example. The sintering temperature in the fourth step ST4 is, for example, 1200°C to 1600°C, or 1300°C to 1500°C. From the viewpoint of mass productivity of the ceramic sheet, suppression of waviness, etc., the average temperature rise rate from the heat treatment temperature in the third step ST3 (i.e., the temperature immediately after the third step ST3) to the sintering temperature is controlled to, for example, 0.1°C / min to 2°C / min. This allows the temperature rise time from the heat treatment temperature (for example, 400°C, 450°C, etc.) to the sintering temperature to be set to 8 hours to 30 hours. The temperature rise time may be 10 hours or more, 12 hours or more, 15 hours or more, 28 hours or less, 25 hours or less, or 20 hours or less. The fourth step ST4 is performed, for example, in an air atmosphere or a low oxygen concentration atmosphere.
[0041] From the viewpoint of mechanical strength, performance, etc., the thickness of the ceramic sheet is 50 μm or more and 200 μm or less. The thickness may be 150 μm or less, 120 μm or less, 100 μm or less, or 80 μm or less. The relative density of the ceramic sheet is 98% or more. The relative density may be 99% or less, or 98.5% or less.
[0042] In one embodiment, the ceramic sheet is a zirconia sheet mainly made of stabilized zirconia powder. From the viewpoint of electrical conductivity (ion conductivity) as an electrolyte sheet, the content of zirconia-based oxide in the zirconia sheet is, for example, 80% by mass or more with respect to 100% by mass of the zirconia sheet. The content may be 90% by mass or more, 95% by mass or more, 97% by mass or more, or 99% by mass or more. The stabilized zirconia powder may be a cubic stabilized zirconia powder or a tetragonal stabilized zirconia powder. In this case, the ratio (%) of cubic crystals measured by X-ray diffraction measurement of the ceramic sheet may be 50% or more, and the ratio (%) of tetragonal crystals may be 50% or more.
[0043] In one embodiment, the rigidity of the ceramic sheet measured by a free resonance method in accordance with ASTM C623-92 may be 60 GPa or more and 90 GPa or less. The rigidity is an index showing the degree of resistance to dimensional change (deformation) due to bending or twisting. By controlling the rigidity of the ceramic sheet within the above range, the breakage rate during processing of the ceramic sheet can be reduced.
[0044] In one embodiment, the waviness of the ceramic sheet is preferably low, for example, 20% or less. The waviness may be 12% or less, 10% or less, 7% or less, or 5% or less. The presence or absence of waviness in the ceramic sheet is confirmed, for example, by visual inspection. The waviness occurrence rate of the ceramic sheet is obtained, for example, by dividing the number of sheets confirmed to have waviness by the number of sheets inspected.
[0045] The degreased body manufactured by the method for manufacturing a ceramic sheet according to the embodiment described above has relatively large pores. In other words, when the pore size distribution of the degreased body is measured by mercury intrusion porosimetry, the total volume of the pores of the degreased body in the pore diameter range of 0.003 μm to 1 μm is 0.17 ml / g to 0.23 ml / g, and the total volume of the pores having a pore diameter of 0.015 μm to 1 μm smaller than the mode diameter of the pores in the above range is 5% to 40% of the total volume, and / or, in the cumulative pore size distribution, when the cumulative 5% pore diameter on a volume basis from the largest pore is D5, the cumulative 50% pore diameter is D50, and the cumulative 95% pore diameter is D95, the following relationship is satisfied: (D5-D95) / D50≧0.56. By firing the degreased body satisfying such conditions, the generation of waviness in the ceramic sheet is suppressed. The reason why the generation of undulation of the ceramic sheet is suppressed is presumed to be as follows. That is, when the degreased body produced by the above-mentioned manufacturing method is fired, the presence of the above-mentioned relatively large pores increases the room for the ceramic powder, which is the main component of the degreased body, to move inside the sheet. For this reason, it is presumed that the stress caused by the shrinkage of the degreased body is alleviated, and the generation of undulation of the ceramic sheet is suppressed. In addition, since the above-mentioned relatively large pores are also filled during the above-mentioned shrinkage, the pores originating from the above pores in the ceramic sheet disappear. As a result, the ceramic sheet becomes dense. Therefore, even if relatively large pores are intentionally provided in the degreased body in order to suppress the generation of undulation of the ceramic sheet, the quality of the ceramic sheet, such as the mechanical strength, is unlikely to deteriorate. Therefore, according to the manufacturing method of one embodiment, the generation of undulation of the ceramic sheet can be suppressed without deteriorating the quality of the ceramic sheet.
[0046] In one embodiment, the sintering temperature in the fourth step ST4 may be 1300° C. or more and 1500° C. or less. In this case, a good ceramic sheet can be obtained.
[0047] In one embodiment, in the fourth step ST4, the time required for heating from the temperature immediately after the third step ST3 (e.g., 400°C, 450°C, etc.) to the sintering temperature may be 8 hours or more and 20 hours or less. Even with such a short firing time, the generation of waviness in the ceramic sheet can be suppressed, thereby improving production efficiency.
[0048] In one embodiment, the relative density of the ceramic sheet may be 95% or more, or 98% or more. The relative density may be 100%, 99.5% or less, or 99% or less. In this case, the mechanical strength required for the ceramic sheet can be suitably obtained.
[0049] The above embodiment describes one aspect of the present disclosure. Therefore, the present disclosure may be modified without being limited to the above embodiment. EXAMPLES
[0050] The present disclosure will be described in more detail below by way of examples, but the present disclosure is not limited to these examples.
[0051] <Example 1> (Preparation of green sheets) As the raw powder, a stabilized zirconia powder (manufactured by Daiichi Kigenso Kagaku Kogyo Co., Ltd., product name "10Sc1CeSZ", D50: about 0.5 μm) in which 10 mol % scandium oxide and 1 mol % cerium oxide are dissolved was used. 100 parts by mass of this raw powder, 2 parts by mass of a commercially available polycarboxylate-type polymer dispersant as a dispersant, and 50 parts by mass of a mixed solvent of toluene / ethyl acetate (mass ratio = 1:1) as a solvent were placed in a nylon mill loaded with zirconia balls. Then, the mixture was milled for 1 hour to prepare slurry I. Next, 18.5 parts by mass of a binder (number average molecular weight: 100,000, glass transition temperature: 0 ° C.) made of a methacrylic copolymer in terms of solid content and 2.0 parts by mass of dibutyl phthalate as a plasticizer were placed in the nylon mill containing the slurry I, and milled again for 15 hours to prepare slurry II. The obtained slurry was transferred to a jacketed round-bottom cylindrical vacuum degassing vessel equipped with an anchor-shaped stirrer, and concentrated and degassed under reduced pressure at a jacket temperature of 40°C while rotating the stirrer at a speed of 30 rpm, and the viscosity at 25°C was adjusted to 3 Pa·s to prepare a raw material slurry for coating. This raw material slurry was continuously coated on a PET film as a base film in a coating device by the doctor blade method. In the same coating device, the coating film on the PET film was dried at 100°C for about 1 hour to obtain a long solid electrolyte green sheet with a thickness of about 0.15 mm. This long green sheet was punched out with a Thomson blade with a side of about 160 mm and peeled off from the PET film to obtain a roughly square green sheet.
[0052] (Preparation of degreased body) Two 180 mm square alumina porous sheets (porosity: 45%, thickness: 0.2 mm) were stacked on a baking shelf. The green sheet was then placed on the two stacked alumina porous sheets. At this time, the green sheet was placed on the alumina porous sheet so that the surface of the green sheet that was in contact with the PET film was facing up. Thereafter, the green sheet and the alumina porous sheet were alternately stacked a total of 10 sheets each, using the alumina porous sheet of the above dimensions as a spacer sheet. Finally, another similar alumina porous sheet was placed on the top alumina porous sheet to form a laminate. Then, 10 sets of laminates were prepared. Next, the temperature was raised to 400°C over 30 hours in a batch-type hot air circulation electric furnace, and multiple degreased bodies were obtained.
[0053] (Ceramic sheet fabrication) The 10 degreased laminates were transferred to a batch-type sintering furnace, where the temperature was raised from room temperature to 400°C over 3 hours, and then from 400°C to 1430°C over 24 hours. The temperature was then held at 1430°C for 3 hours, and cooled to 900°C over 6 hours. The sheets were then allowed to cool to room temperature in the sintering furnace, producing ceramic sheets with sides of approximately 120 mm and a thickness of 110 μm. The relative density of the ceramic sheet of Example 1 is shown in Table 1 below.
[0054] <Example 2> A degreased body was produced in the same manner as in Example 1, except that the binder was 18 parts by mass in terms of solid content, the dispersant was 3 parts by mass, the milling time for preparing slurry I was 15 minutes, the milling time for preparing slurry II was 3 hours, and the thickness of the green sheet was 240 μm. A ceramic sheet with a side length of about 120 mm and a thickness of 180 μm was produced. The relative density of the ceramic sheet in Example 2 is shown in Table 1 below.
[0055] <Example 3> A degreased body was produced in the same manner as in Example 1, except that the binder was 17.25 parts by mass in terms of solid content, the dispersant was 3 parts by mass, 60 parts by mass of a mixed solvent of toluene / ethyl acetate / 1-butanol (1-BuOH) (mass ratio = 1:1:2) was used as the solvent, and the thickness of the green sheet was 240 μm. A ceramic sheet with a side length of about 120 mm and a thickness of 180 μm was also produced. The relative density of the ceramic sheet of Example 3 is shown in Table 1 below.
[0056] <Example 4> A ceramic sheet having a side length of about 120 mm and a thickness of 100 μm was produced in the same manner as in Example 3, except that the temperature of the degreased body produced under the conditions described in Example 3 was raised from 400° C. to 1450° C. over 15 hours. The relative density of the ceramic sheet of Example 4 is shown in Table 1 below.
[0057] <Example 5> A stabilized zirconia powder containing 6 mol% scandium oxide dissolved therein (manufactured by Daiichi Kigenso Kagaku Kogyo Co., Ltd., product name "6ScSZ", D50: 0.5 μm) was used as the raw material powder, the binder was 16.5 parts by mass in terms of solid content, the dispersant was 1.8 parts by mass, the temperature was raised from 400 ° C to 1380 ° C over 24 hours, and the thickness of the green sheet was 95 μm. A degreased body was produced in the same manner as in Example 1, and a ceramic sheet with a side length of about 120 mm and a thickness of 70 μm was produced. The relative density of the ceramic sheet of Example 5 is shown in Table 1 below.
[0058] <Example 6> A degreased body was produced in the same manner as in Example 1, except that a stabilized zirconia powder (Tosoh Corporation, product name "3YSZ", D50: 0.7 μm) in which 3 mol % yttrium oxide was dissolved was used as the raw material powder, the binder was 17 parts by mass in terms of solid content, the dispersant was 2.5 parts by mass, the temperature was raised from 400°C to 1490°C over 24 hours, and the green sheet thickness was 75 μm. A ceramic sheet with a side length of about 120 mm and a thickness of 55 μm was produced. The relative density of the ceramic sheet of Example 6 is shown in Table 1 below.
[0059] <Example 7> A ceramic sheet with a side length of about 120 mm and a thickness of 70 μm was produced in the same manner as in Example 5, except that the temperature of the degreased body produced under the conditions described in Example 5 was raised from 400° C. to 1380° C. over a period of 9 hours. The relative density of the ceramic sheet of Example 7 is shown in Table 1 below.
[0060] <Comparative Example 1> A degreased body was prepared in the same manner as in Example 1, except that the binder was 17.5 parts by mass in terms of solid content, and the dispersant was 3 parts by mass, and a ceramic sheet having a side length of about 120 mm and a thickness of 110 μm was also prepared. The relative density of the ceramic sheet of Comparative Example 1 is shown in Table 1 below.
[0061] <Comparative Example 2> A degreased body was prepared in the same manner as in Example 5, except that the amount of the dispersant was 3 parts by mass, and a ceramic sheet having a side length of about 120 mm and a thickness of 70 μm was also prepared. The relative density of the ceramic sheet of Comparative Example 2 is shown in Table 1 below.
[0062] <Comparative Example 3> A ceramic sheet with a side length of about 120 mm and a thickness of 110 μm was produced in the same manner as in Comparative Example 1, except that the temperature of the degreased body produced under the conditions described in Comparative Example 1 was raised from 400° C. to 1430° C. over a period of 9 hours. The relative density of the ceramic sheet of Comparative Example 3 is shown in Table 1 below.
[0063] (Pore size distribution by mercury intrusion method) The distribution of pore diameters from 0.003 μm to 1 μm (pore diameter distribution) of the degreased bodies of Examples 1 to 7 and Comparative Examples 1 to 3 was measured by mercury intrusion using an automatic mercury porosimeter (AutoPore IV9520, manufactured by Micromeritics Instrument Corporation). As a result, the total volume of pores, the total volume of pores having a pore diameter 0.015 μm or more larger than the mode diameter of the pores, and the cumulative pore diameter distribution were measured for each Example and Comparative Example. The measurement results of the total volume and the total volume, the ratio of the total volume to the total volume (volume ratio: total volume / total volume), and (D5-D95) / D50 for each Example and Comparative Example are shown in Table 1 below.
[0064] (Waviness measurement) The waviness occurrence rate was measured for each of the ceramic sheets of Examples 1 to 7 and Comparative Examples 1 to 3. (The presence or absence of waviness was confirmed by visual inspection for all fired ceramic sheets excluding sheets that were cracked during firing, and the waviness occurrence rate was determined by dividing the number of sheets with waviness by the number of sheets inspected.) The measurement results of the waviness occurrence rate for each Example and Comparative Example are shown in Table 1 below.
[0065] [Table 1]
[0066] FIG. 2 is a diagram showing the pore size distribution of each Example and each Comparative Example. In FIG. 2, a graph 11 showing the measurement results of Example 1, a graph 12 showing the measurement results of Example 2, a graph 13 showing the measurement results of Examples 3 and 4, a graph 14 showing the measurement results of Examples 5 and 7, a graph 15 showing the measurement results of Example 6, a graph 16 showing the measurement results of Comparative Examples 1 and 3, and a graph 17 showing the measurement results of Comparative Example 2 are shown. FIG. 3 is a diagram showing the cumulative pore size distribution of each Example and each Comparative Example. In FIG. 3, a graph 21 showing the measurement results of Example 1, a graph 22 showing the measurement results of Example 2, a graph 23 showing the measurement results of Examples 3 and 4, a graph 24 showing the measurement results of Examples 5 and 7, a graph 25 showing the measurement results of Example 6, a graph 26 showing the measurement results of Comparative Examples 1 and 3, and a graph 27 showing the measurement results of Comparative Example 2 are shown. In each of FIG. 2 and FIG. 3, the horizontal axis shows the pore size, and the vertical axis shows the pore volume. As shown in FIG. 2 and FIG. 3, graphs 11 to 15 and 21 to 25 all tend to have a higher proportion of large pores than graphs 16, 17, 26 and 27. [Explanation of symbols]
[0067] 11~17, 21~27...Graph.
Claims
1. A method for producing a ceramic sheet, comprising: preparing a slurry by mixing a ceramic powder, a solvent and a binder; forming a green sheet by applying the slurry to a sheet and then drying the sheet; forming a degreased body of the green sheet by degreasing the green sheet; sintering the degreased body to form the ceramic sheet; Equipped with When the pore size distribution of the degreased body is measured by mercury intrusion porosimetry, the total volume of pores in the degreased body in the pore size range of 0.003 μm or more and 1 μm or less is 0.17 ml / g or more and 0.23 ml / g or less; The total volume of pores having a pore diameter of 0.015 μm or more and 1 μm or less, which is smaller than the mode diameter of the pores in the range, is 5% or more and 40% or less of the total volume. A method for manufacturing a ceramic sheet.
2. A method for producing a ceramic sheet, comprising: preparing a slurry by mixing a ceramic powder, a solvent and a binder; forming a green sheet by applying the slurry to a sheet and then drying the sheet; forming a degreased body of the green sheet by degreasing the green sheet; sintering the degreased body to form the ceramic sheet; Equipped with When the pore size distribution of the degreased body is measured by mercury intrusion porosimetry, the total volume of pores in the degreased body in the pore size range of 0.003 μm or more and 1 μm or less is 0.17 ml / g or more and 0.23 ml / g or less; In the cumulative pore size distribution, when the cumulative 5% pore size based on the volume from the largest pore is defined as D5, the cumulative 50% pore size is defined as D50, and the cumulative 95% pore size is defined as D95, (D5-D95) / D50≧0.56 is satisfied. A method for manufacturing a ceramic sheet.
3. 3. The method for producing a ceramic sheet according to claim 1, wherein the ceramic powder is a stabilized zirconia powder containing at least one rare earth element selected from the group consisting of scandium, yttrium, and cerium in a total amount calculated on oxide of 3 mol % to 15 mol %.
4. The method for producing a ceramic sheet according to claim 1 or 2, wherein a sintering temperature in the step of sintering the degreased body is 1300° C. or higher and 1500° C. or lower.
5. 5. The method for producing a ceramic sheet according to claim 4, wherein in the step of sintering the degreased body, a temperature rise time from a temperature immediately after the step of forming the degreased body to the sintering temperature is 8 hours or more and 20 hours or less.
6. The method for producing a ceramic sheet according to claim 1 or 2, wherein the ceramic sheet has a relative density of 98% or more.
7. The method for producing a ceramic sheet according to claim 1 or 2, wherein the ceramic sheet has a thickness of 50 μm or more and 200 μm or less.
8. A degreased body of a green sheet, When the pore size distribution of the degreased body is measured by mercury intrusion porosimetry, the total volume of pores in the degreased body in the pore size range of 0.003 μm or more and 1 μm or less is 0.17 ml / g or more and 0.23 ml / g or less; The total volume of pores having a pore diameter of 0.015 μm or more and 1 μm or less, which is smaller than the mode diameter of the pores in the range, is 5% or more and 40% or less of the total volume. Defatted body.
9. A degreased body of a green sheet, When the pore size distribution of the degreased body is measured by mercury intrusion porosimetry, the total volume of pores in the degreased body in the pore size range of 0.003 μm or more and 1 μm or less is 0.17 ml / g or more and 0.23 ml / g or less; In the cumulative pore size distribution, when the cumulative 5% pore size based on the volume from the largest pore is defined as D5, the cumulative 50% pore size is defined as D50, and the cumulative 95% pore size is defined as D95, (D5-D95) / D50≧0.56 is satisfied. Defatted body.
Citation Information
Patent Citations
Manufacturing method of scandia-stabilized zirconia sheet for solid oxide fuel cell
JP2011204398A